Physiological responses and tolerance of three acacia species to cadmium stress during germination and early seedling growth - Davis, La Ode Muhammad Muchdar; Nurhasanah; Juhaeti, Titi; Gunawan, Indra (Penerbit Universiti Kebangsaan Malaysia, 2024)
Soil contamination with cadmium (Cd) is a serious threat to ecosystems. Phytoremediation is a cost-effective green technology that can be used to clean up Cd pollution, and Acacia species are potential phytoremediation agents due to their fast growth, significant biomass, and tolerance to environmental stresses. Most studies of Cd stress on Acacia focused on later vegetative stages and the tolerances during germination and early seedling are elusive. This study aimed to assess the tolerance of Acacia mangium, Acacia crassicarpa, and Acacia auriculiformis to Cd stress during germination and early seedling growth. In response to 250 μM Cd treatment, A. auriculiformis germination was slightly increased compared to the control. Leaf organ formation remained largely unaffected by Cd stress, except for the true leaf number in A. mangium, which was significantly higher in response to 125 µM Cd than those to 250 µM Cd treatment and control at 8 and 10 weeks after treatment. The onset of phyllode development transition from true leaf was significantly delayed in A. mangium compared with the other two Acacia, irrespective of the presence of Cd. There were no significant differences in leaf gas exchange parameters (photosynthesis, stomatal conductance, and transpiration), leaf-level water use efficiency, or leaf chlorophyll content between Cd-treated and control plants, suggesting that the three Acacia species are tolerant to Cd at both germination and early seedling phases. Cd accumulation during the experiment was very low in A. mangium seedlings (2.8 mg kg-1 upon 250 µM Cd) and insignificant in A. crassicarpa and A. auriculiformis, indicating non-hyperaccumulation or Cd exclusion at the seedling stage.